PENILAIAN WISATAWAN PADA FASILITAS ANDALUS WISATA KELUARGA KABUPATEN KAMPAR PROVINSI RIAU - Agus Saputra; Andri Sulistyani (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2021)
Increasing tourist facilities is one way for tourist attractions to bring in more tourists. Tourist ratings on the facilities of a tourist attraction can be used as a benchmark for improving tourist attraction facilities. This study aims to determine the rating of tourists on the facilities in Andalus Family Tourism, Kampar Regency, Riau Province, as well as to determine the efforts of the manager in managing the Andalus Family Tourism facilities. This study uses a quantitative method with a descriptive approach to describe and explain the situation that occurs based on data collection techniques of observation, questionnaires, documentation, and interviews which then draws a conclusion. The sample in this study was 100 people using the slovin formula, namely tourists who had visited Andalus Family Tourism in 2020. The key informant in this study was the chairman of the Andalus Family Tourism manager. Based on the results of the study, it can be concluded that tourist ratings at Andalus Family Tourism facilities in Kampar Regency, Riau Province are good in almost all types of facilities, namely main facilities, supporting facilities, service facilities, management facilities, and complementary facilities which refer to the grand theory used. This is evidenced by the results of the assessment score which got a good score with a score of 22,867. Efforts by the manager in managing the facilities are to make gradual improvements to existing facilities as well as to increase the quantity and quality of Andalus Family Tourism facilities. Keywords: facilities, Andalus, family tourism